Dampak Work-Life Balance, Motivasi Kerja, terhadap Kinerja Karyawan: Tinjauan Sistematis Tempat Kerja di Indonesia - Saputra, Anggi Firmanjaya; Masdupi, Erni (Pedagogi: Jurnal Ilmu Pendidikan, 2024)
This study explores the impact of work-life balance and work motivation on employee performance within organizational contexts in Indonesia. Using a systematic literature review approach based on PRISMA, the study analyzes 64 peer-reviewed articles published between 2020 and 2024. The findings reveal that work-life balance, facilitated by flexible policies and supportive supervisor behavior, significantly enhances employee engagement and productivity. Work motivation, both intrinsic and extrinsic, also plays a crucial role in achieving optimal performance through internal incentives such as personal satisfaction and external support like organizational encouragement. In Indonesia’s collectivist culture, social and familial values strongly influence the relationship between work-life balance, work motivation, and employee performance. This study highlights the importance of organizational strategies, such as flexible work arrangements and supportive leadership, in fostering a conducive and productive work environment. It provides practical insights for organizations in designing balanced policies to sustainably improve employee well-being and performance.